Expression of the autoantigen TRIM33/TIF1γ in skin and muscle of patients with dermatomyositis is upregulated, together with markers of cellular stress. (1st August 2017) - Scholtissek, B.; Ferring‐Schmitt, S.; Maier, J.; Wenzel, J.
Summary: Dermatomyositis (DM) is an autoimmune disorder associated with a dysregulation of immune homeostasis of both the innate and adaptive immune system. Earlier data suggested that these two arms of the immune system interconnect in DM. In the current study, we analysed the association of autoantigen expression [adaptive system components: Mi2, transcriptional intermediary factor (TIF)1γ, small ubiquitin‐like modifier 1 activating enzyme subunit (SAE)1, melanoma differentiation‐associated protein (MDA)5] with markers of cellular stress (innate system components: MxA, p53) in skin and muscle (immunohistology and gene expression data, respectively). We found that distinctive self‐antigens of DM were elevated in both skin and muscle tissue. In particular, TIF1γ expression was seen in autoimmune diseases including DM, but not in other inflammatory skin disorders. This upregulation was closely associated with p53 expression and type I interferon‐regulated inflammation, suggesting that upregulation of autoantigens in the skin and muscle of patients with DM might be driven by cellular stress. Better understanding of these mechanisms could pave the way for new therapeutic concepts focusing on stress reduction.